Factors associated with exclusive breastfeeding in children under four months old in Botucatu-Sp, Brazil - Barros Leite Carvalhaes, Maria Antonieta de [UNESP]; De Lima Paradal, Cristina Maria Garcia [UNESP]; Da Costa, Marilene Plicido (Universidade de São Paulo (USP), 2007)
This study aimed to identify factors associated with exclusive breastfeeding (AME) and the reasons mothers presented to introduce complementary feeding in the first four months of life. A total of 380 mothers (92.2%) of children under four months old vaccinated in a Multi-vaccination Campaign were interviewed. To identify factors associated to AME, univariate and multiple logistic regressions analyses were performed. Thirty-eight percent of the children were on AME; 33.4% consumed cow milk; 29.2% tea; and 22.4% water. The mothers justified introduction of cow milk by factors related to quantity/quality of maternal milk and necessity of the child. The use of a pacifier (odds ratio=2.63; CI95%=1.7-4.06) and difficulty to breastfeed (odds ratio=1.57., CI95%=1.02-2.41) were associated with the absence of AME. The populational attributable risk percentage for the use of a pacifier was estimated at 46.8%. Thus, modifiable risk factors were associated with AME interruption.
Keywords: breast feeding; human milk; weaning; risk factors